2006
DOI: 10.1590/s0066-782x2006001500007
|View full text |Cite
|
Sign up to set email alerts
|

Análise de registros eletrocardiográficos associados ao infarto agudo do miocárdio

Abstract: OBJECTIVEEvaluate correlations between variations in eletrocardiogram (ECG) recordings and acute myocardial infarction. METHODSUse of a low-cost software to digitalize printed and/or ".pdf" fi le format ECG recordings. Calculation of STsegment area and amplitudes of the J and Y points. RESULTSThe amplitude of the Y point holds maximum correlation with troponin concentration. ST-segment elevation is not a good statistical indicator of myocardial infarction severity. There is a strong negative correlation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
(9 reference statements)
2
4
0
2
Order By: Relevance
“…About 50% of the AMI cases showed a change in the ECG tracing with ST-segment elevation. In this study, of the three confirmed cases, two had altered electrocardiograms, that is, 66.7%, similar to the study by Mansur et al 10 . The same authors 10 stated that there was a 91% specificity of the diagnosis by this method, which may justify why no tissue necrosis markers test, also called cardiac enzymes, was performed in the UCU.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…About 50% of the AMI cases showed a change in the ECG tracing with ST-segment elevation. In this study, of the three confirmed cases, two had altered electrocardiograms, that is, 66.7%, similar to the study by Mansur et al 10 . The same authors 10 stated that there was a 91% specificity of the diagnosis by this method, which may justify why no tissue necrosis markers test, also called cardiac enzymes, was performed in the UCU.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, of the three confirmed cases, two had altered electrocardiograms, that is, 66.7%, similar to the study by Mansur et al 10 . The same authors 10 stated that there was a 91% specificity of the diagnosis by this method, which may justify why no tissue necrosis markers test, also called cardiac enzymes, was performed in the UCU. The study showed that the cardiac causes are not the first cause of chest pain, and among the cardiac causes AMI is one of the diseases, but there are others, as also identified in a study by Barbosa et al 4 .…”
Section: Discussionsupporting
confidence: 90%
“…In this study, education, gender and age were not determining in the analysis of the time patients took to seek for a cardiac service. However, literature shows that women and elderly people take more time to go to an emergency service (6,8,12) . This study also showed a longer average time for patients who used ambulance services in relation to the others, and this fact contradicts other studies which state that the average time from the beginning of the pain to the moment they get to the emergency service decreases when using ambulance services (9)(10) .…”
Section: Average Delta T In the Usa Was 3hr50min; In Southmentioning
confidence: 99%
“…One study states that patients in Brazil do not seek healthcare services promptly because they do not recognize AMI symptoms, because they do not accept what they are feeling, because first aid is not specialized and because of bad public transportation (6) . Identifying the reasons why patients delay the search for health services is important because, based on these data, nursing professionals can interfere and educate patients, their relatives and the community.…”
Section: Introductionmentioning
confidence: 99%
“…Além da variação alta na precisão dos diagnósticos, quando se analisa os equipamentos para exames cardíacos e pessoal qualificado, percebe-se que ainda há uma boa quantidade de eletrocardiógrafos analógicos, principalmente na rede pública de hospitais e ainda há uma carência de profissionais qualificados para dar conta da demanda de exames feitos, pondera-se, então, que a tecnologia pode ajudar a encontrar soluções para alguns destes problemas. (Mansur, 2006). Focado na tentativa de ajudar a diminuir o quadro de óbitos causados pelas doenças cardíacas, amenizar a falta de profissionais e viabilizar o uso de equipamentos antigos, optou-se pelo desenvolvimento de uma aplicação que pudesse atender a estes quesitos.…”
Section: Introductionunclassified